A Review Paper on Various Wireless Network Attacks (International Journal of Food and Nutritional Sciences, 2022)
Security for wireless sensor networks (WSNs) is becoming increasingly crucial due to the growth of several security-sensitive applications using WSNs in a range of industries. WSNs have a number of extra weaknesses as compared to conventional wireless and wired networks, such as shifting network topology, the broadcast nature of the medium, resource-constrained nodes, huge network size, and a lack of physical infrastructure. WSNs are more vulnerable to a range of attacks than cable communications because of their open communication environment, including passive eavesdropping operations that result in intercepted transmissions and active jamming attacks that interrupt transmissions. The opponent may now carry out more severe and sophisticated attacks thanks to these additional vulnerabilities. Therefore, a thorough analysis of potential WSN attacks is required. Therefore, the goal of this article is to look at wireless security flaws and threats in order to come up with a reliable and efficient defensive strategy for enhancing WSN security. First, we will go through wireless network security issues and requirements. The paper then goes on to talk about wireless network security flaws and how to classify possible attacks in WSNs based on OSI protocol levels. Finally, future work in WSN security is discussed, as well as many remaining technical issues that remain unsolved.